The Effect of Seaweed Eucheuma cottonii on Superoxide Dismutase (SOD) Liver of Hypercholesterolemic Rats - TUTIK WRESDIYATI; ANS BUDI HARTANTA; MADE ASTAWAN (Bogor Agricultural University, Indonesia, 2008)
Intracellular antioxidant superoxide dismutase (SOD) was reported decreased in the liver and kidney of hypercholesterolemic rats. This study was conducted to observe the effect of seaweed Eucheuma cottonii powder on the profile of blood cholesterol and the level of SOD in liver tissues of hypercholesterolemic rats by using immunohistochemical technique. Twenty male Wistar rats were used for this study. Those rats were divided into four groups; (i) negative control group (A), (ii) hypercholesterolemia group treated by 5% seaweed powder (B), (iii) hypercholesterolemia group treated by 10% seaweed powder (C), and (iv) Positive control group or hypercholesterolemia group (D). The experiment was carried out for 35 days. Hypercholesterolemia condition (> 130 mg/dl), except group A, was achieved by feeding the rats with commercial diet containing 1% cholesterol. Drinking water was given ad libitum for 40 days. The results showed that seaweed powder decreased the total cholesterol, low density lipoprotein (LDL), triglyceride, and increased the level of high density lipoprotein (HDL) and SOD status in the liver tissues of hypercholesterolemic rats. The treatment of 10% seaweed powder gave better results than that of 5%. These results suggested that dietary fiber such in the seaweed powder has antioxidant activity. Key words: superoxide dismutase (SOD), seaweed-Eucheuma cottonii, hypercholesterolemia, liver, immunohistochemistry